Behavioural mediators of reduced energy intake in a physical activity, diet, and sleep behaviour weight loss intervention in adults. (1st October 2021) - Fenton, Sasha; Burrows, Tracy L.; Collins, Clare E.; Holliday, Elizabeth G.; Kolt, Gregory S.; Murawski, Beatrice; Rayward, Anna T.; Stamatakis, Emmanuel; Vandelanotte, Corneel; Duncan, Mitch J.
Abstract: Reduced energy intake is a major driver of weight loss and evidence suggests that physical activity, dietary, and sleep behaviours interact to influence energy intake. Energy restriction can be challenging to sustain. Therefore to improve intervention efficacy, evaluation of how changes in physical activity, diet, and sleep behaviours mediate reduced energy intake in adults with overweight/obesity who participated in a six-month multiple-behaviour-change weight loss intervention was undertaken. This was a secondary analysis of a 3-arm randomised controlled trial. Adults with body mass index (BMI) 25–40 kg/m 2 were randomised to either: a physical activity and diet intervention; physical activity, diet, and sleep intervention; or wait-list control. Physical activity, dietary intake, and sleep was measured at baseline and six-months using validated measures. The two intervention groups were pooled and compared to the control. Structural equation modelling was used to estimate the mediated effects (AB Coefficient) of the intervention on total energy intake. One hundred and sixteen adults (70% female, 44.5y, BMI 31.7 kg/m 2 ) were enrolled and 70% (n = 81) completed the six-month assessment. The significant intervention effect on energy intake at six-months (−1011 kJ/day, 95% CI -1922, −101) was partially mediated by reduced fat intake (AB = −761.12, 95% CI -1564.25, −53.74) and reduced consumption of energy-dense, nutrient-poor foods (AB = −576.19, 95% CI -1189.23, −97.26). In this study, reducing fat intake and consumption of energy-dense, nutrient-poor foods was an effective strategy for reducing daily energy intake in adults with overweight/obesity at six-months. These strategies should be explicitly targeted in future weight loss interventions.